Facing The Digital Revolution: Challenges And Opportunities For Teaching English in The Era Of MOOCs - Andy Endra Krisna (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The digital revolution has had a significant impact on the world of education, including English language teaching. Information and communication technologies (ICTs) enable more flexible and interactive learning through online platforms such as Massive Open Online Courses (MOOCs), which provide global access to education at low or no cost. Although MOOCs offer great opportunities, challenges such as the digital divide and integration with traditional curricula remain barriers. Teaching English in the digital era requires innovative approaches that incorporate technology, such as computer-assisted learning (CALL) and AI-based applications, to enhance students' linguistic skills. The role of teachers has also changed, from being a presenter of material to a facilitator who guides students in utilizing digital learning resources. With adequate training and digital literacy support, teachers can integrate technology into learning to create a more relevant and effective learning experience. Adapting to these changes is essential to improving the quality of education in the digital era.